A obesidade na infância e o protagonismo da educação física escolar - Luana dos Santos Ribeiro; Felipe da Silva Triani (Universidade Estadual do Oeste do Paraná, 2016)
This article intends to present a point of view on the role of Physical School Education in the fight against obesity. This study presents some factors that contribute to this multifactorial problem, among them the reduction of physical activity, the excess of time spent in video and technological toys, psychological disorders and inadequate feeding, elements acquired during childhood and that physical education classes can help to minimize this process through health awareness. Therefore, although physical education classes are not sufficient in terms of direct protection against obesity, their role is presented in conceptual and attitudinal terms, as it creates space within the classes to discuss the problem of obesity and motivate critical awareness about its effects encouraging children and adolescents to adopting new and beneficial habits of physical activity and health care.